The Role of Digital Identification in Agriculture : Emerging Applications - World Bank (World Bank, Washington, DC, 2019)
Agricultural development is one of the most powerful tools to end extreme poverty. Agriculture accounts for nearly one-third of global gross domestic product (GDP), and the majority of the world’s poor live in rural areas and make a living through agriculture. To end extreme poverty by 2030, most of the income gains will need to be made in rural areas, including by boosting smallholder farmers’ earnings from farming and off-farm activities.1 Increasing the ability of such smallholders to professionalize, improve their productivity, and generate additional income is therefore critical to both alleviate rural poverty and increase food security. Smallholder families have complex livelihoods. They typically rely on income from a variety of sources,including government safety nets, subsidies, and off-farm enterprises. Enabling these families to exit poverty will require innovative solutions to address critical challenges, such as (1) lack of access to financial services, (2) lack of adequate supply-chain traceability, (3) challenges related to the delivery of goods and services, and (4) gender inequality. When smallholder farmers lack government recognized identification (ID) documents, these and other challenges are further exacerbated. Without an official proof of identity, many smallholder farmers struggle to access services and subsidies and to seize new opportunities offered by innovations in mobile technologies, finance, and beyond. A robust, government recognized ID can help smallholder farmers formally register land and livestock, and access mobile, financial, and other services that would allow them to work, sell, and spend income formally. Thus, identification is an important building block to achieving Sustainable Development Goal 2: End hunger, achieve food security and improved nutrition, and promote sustainable agriculture. This paper looks at three key applications of identification in agriculture to understand how these can help tackle some of the critical challenges, remove barriers to agricultural productivity, and enhance farmers’ livelihoods, including through: (1) increasing the effectiveness and inclusivity of subsidy programs; (2) enabling formal land and asset registration; and (3) improving data about farmers’ economic activity and needs. At the same time, there are challenges to maximizing the benefits of identification in agriculture. ID systems increasingly rely on digital infrastructures for authentication and identity verification. Although mobile and broadband coverage is growing at a rapid rate worldwide, rural areas often still lack the reliable mobile and Internet connectivity required for certain applications of digital IDs. Rural households are also less likely to have the digital literacy required to navigate digital ID systems and may be less able to monitor and hold authorities accountable for how their personal data are being used and shared. Therefore, any ID application in agriculture will need to consider how data protection and privacy safeguards may need to be adapted to rural contexts. In addition, ID applications in agriculture may face institutional arrangements and coordination challenges. In the presence of a foundational ID system, the Ministry of Agriculture or other implementer will need to coordinate with other areas of the government, including the ID provider. In the absence of a foundational ID system, the Ministry of Agriculture or other implementer will need to consider how they can meet their own needs while coordinating with other agencies and partners who may be implementing separate yet overlapping functional ID systems.